Increased In Vivo Expression of an Inflammatory Marker in Temporal Lobe Epilepsy - Hirvonen, Jussi; Kreisl, William C.; Fujita, Masahiro; Dustin, Irene; Khan, Omar; Appel, Shmuel; Zhang, Yi; Morse, Cheryl; Pike, Victor W.; Innis, Robert B.; Theodore, William H. (Journal of Nuclear Medicine, 2012)
Animal studies and clinical observations suggest that epilepsy is associated with inflammation. Translocator protein (TSPO) (18 kDa), a marker of inflammation, is increased in vitro in surgical samples from patients with temporal lobe epilepsy. TSPO can be measured in the living human brain with PET and the novel radioligand (11)C-PBR28. In this study, we sought to determine whether in vivo expression of TSPO is increased ipsilateral to the seizure focus in patients with temporal lobe epilepsy. Sixteen patients with unilateral temporal lobe epilepsy and 30 healthy subjects were studied with (11)C-PBR28 PET and MRI. Uptake of radioactivity after injection of (11)C-PBR28 was measured from regions of interest drawn bilaterally onto MR images. Brain uptake from ipsilateral and contralateral hemispheres was compared using a paired-samples t test. We found that brain uptake was higher ipsilateral to the seizure focus in the hippocampus, parahippocampal gyrus, amygdala, fusiform gyrus, and choroid plexus but not in other brain regions. This asymmetry was more pronounced in patients with hippocampal sclerosis than in those without. We found increased uptake of radioactivity after injection of (11)C-PBR28 ipsilateral to the seizure focus in patients with temporal lobe epilepsy, suggesting increased expression of TSPO. Studies in larger samples are required to confirm this finding and determine the clinical utility of imaging TSPO in temporal lobe epilepsy.